Validation of the minisequencing method for detection of G1691A (Leiden) factor V mutation. (21st December 2012) - Łaczmański, Łukasz; Ślęzak, Ryszard; Karpiński, Paweł; Kolačkov, Katarzyna; Lebioda, Arleta; Milewicz, Andrzej
Abstract: Introduction : The factor V (FV) plays an important role in the coagulation process and belongs to the group of factors that significantly increases the risk of thrombophilia. Our study presents a novel, rapid method for the detection of FV (R506Q) mutation using minisequencing approach. Material and methods : Samples of peripheral blood were obtained from 300 females of the Lower Silesian population. Minisequencing, as one of the polymerase chain reaction (PCR)-based methods, was used for detection the of FV (R506Q) point mutations. The allele restriction mutation system PCR (ARMS-PCR) verifying method was applied. Results : By using minisequencing reaction we examined the FV genotypes in the female group who experienced at least one unexplained spontaneous miscarriage. The results of the ARMS-PCR, as a verifying test, were fully consistent with the results of the minisequencing technique. Discussion : One of the many factors which may cause thrombophilia is the FV gene mutation R506Q. A full validation of the minisequencing method was carried out in order to apply this method to clinical tests. The validation shows that the minisequencing technique is highly precise and may be used in routine diagnostics of the FV R506Q mutation